Interactivity, game creation, design, learning, and innovation : 5th International Conference, ArtsIT 2016, and first International Conference, DLI 2016, Esbjerg, Denmark, May 2-3, 2016, Proceedings /: 5th International Conference, ArtsIT 2016, and first International Conference, DLI 2016, Esbjerg, Denmark, May 2-3, 2016, Proceedings. (2017) - Unknown
No abstract available